Teacher leaders as teacher educators: recognising the 'educator' dimension of some teacher leaders' practice. Issue 3 (27th May 2021) - Dickerson, Claire; White, Elizabeth; Levy, Roger; Mackintosh, Julia
ABSTRACT: The functions of teacher leaders and teacher educators, what they do, are critical in teacher education. This article presents the seemingly unexamined concept that some teacher leaders' practice includes a teacher educator dimension. Evidence that supports this claim is provided by exploring the interrelationship between teacher leader and teacher educator functions using a focused analysis of the literature and findings from qualitative research. This research investigated the impact of a professional development programme for primary science leaders. Data were collected from strategic-level informants, programme mentors and science leaders using interviews, questionnaires and a focus group. The findings are analysed to provide a critical overview of the participants' views of the requirements for successful leadership and development of primary science and to illustrate how educator and leader functions are intertwined in science leaders' activities. The article considers the implications of recognising the educator dimension of some teacher leaders' practice and asserts that these implications extend beyond the primary science context of the research. Acknowledging the contribution made by 'unrecognised' teacher educators and enabling them to contribute to and gain from the professional knowledge of the teacher educator community has significant potential to enrich practice in teacher education internationally, nationally and locally.